A review of residential water conservation tool performance and influences on implementation effectiveness. - Inman, David; Jeffrey, Paul (Taylor & Francis, 2006)
There has been sparse coverage of advances in the application of Demand-Side Management (DSM) in the academic press in recent years. At the same time a number of important DSM studies have been reported on by non-academic institutions, and there is therefore a need for a comprehensive, up to date review of the impacts of DSM tools and the factors which influence their effectiveness. This paper aims to begin to address this apparent lack of coverage with a review of residential DSM tools using recent reports of DSM campaigns in the western (developed) world collected from a range of sources. The aims are, to understand the potential for residential DSM tools to save water in different types of household under varying conditions and, identify influences on implementation effectiveness. The current review will be of interest to, among others, water company professionals, policy makers, regulators and environmental agencies.
Keywords: Demand-side management; Water saving technology; Water conservation; Household water demand